A Novel Modeling and Scheduling Method for Modern Roundabouts. Issue 3 (2022) - Duan, Peihu; Huang, Lingying; Lv, Yuezu
Abstract: This paper investigates optimal traffic flow scheduling for signalized roundabouts. First, a novel model for roundabouts is introduced based on the discretization of traffic flow. Then, the signal control problem for signalized roundabouts is formulated and further converted into a Markov Decision Process (MDP)-based optimization problem. Some fundamental properties about this problem are revealed. It is anticipated that the proposed modeling and signal designing method can provide an effective technique for traffic flow scheduling issues.